Exotic plants and other habitat characteristics do not impact Veery reproductive success at multiple spatial scales in northeastern Pennsylvania - Christopher B Goguen; Les D Murray (Avian Conservation and Ecology, 2025)
It is expected that birds have evolved nest site preferences that, on average, lead to positive fitness outcomes. It is possible, however, that mismatches occur between these preferences and reproductive success when a population experiences sudden changes in its habitat such as through invasion by exotic plants. From 2012 to 2016, we studied breeding habitat use and nesting success of the Veery ( Catharus fuscescens ) in mature forests of northeastern Pennsylvania that had been invaded by exotic shrubs. Our objectives were to document the prevalence of use of exotic shrubs as nesting substrates in this population, determine if use of exotic shrubs reduced nesting success or other measures of productivity, and to evaluate whether habitat or other characteristics of individual nests were useful predictors of nest survival. Although many native substrates were used, almost 60% of 289 nests used exotic substrates, particularly Japanese barberry ( Berberis thunbergii ) and multiflora rose ( Rosa multiflora ). Estimates of nest survival from logistic exposure modeling, mean clutch size, and mean number of young fledged per successful nest did not differ between nests placed in native versus exotic substrates. Annual nest survival rates varied substantially (range = 0.17–0.44). Nest success was also positively related to the age of a nest and decreased when a nest camera was present. However, survival of individual nests showed little relationship with vegetative/habitat variables at three spatial scales. Overall, exotic shrubs did not appear to negatively impact Veery nesting success and instead appeared to be of similar quality as native plants for nesting substrates.